Adenofibroma of Skene's Duct: A Case Report. (11th April 2010) - Chong, Yosep; Eom, Minseob; Park, Kwang Hwa; Chung, Hyun Chul; Ro, Jae Y.
Abstract : Skene's glands, also known as paraurethral glands, are homologues of the male prostate, in which painless cystic masses and inflammation due to obstruction have been rarely found and reported. In addition, there have been rare reported cases of adenocarcinoma of Skene's glands. Recently, the authors experienced the first case of adenofibroma arising in Skene's glands of a 62-year-old woman with coital pain. Hereby, we present the case with pathologic and immunohistochemical findings and a short review of literature.